EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE (TPS) AND TYPE TWO STAY TWO STRAY (TSTS) ON MATHEMATICS LEARNING OUTCOMES STUDENT CLASS VIII - Fitriani Dyah Wahyuningtyas; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The teacher's learning model can influence the low learning outcomes of students. The research aimed to determine the effectiveness of the cooperative learning model of TPS type with cooperative learning model TSTS type on mathematics outcomes. The population in this study were students of class VIII State Junior High School 2 Patikraja (SMP Negeri 2 Patikraja) consisted of 6 classes. The sampling technique used a random sampling technique to class, obtained class VIII C as experimental class I, which uses a cooperative learning model of type TPS and VIII B as experiment class II, which uses a cooperative learning model of type TSTS. Data collection techniques used were documentation and tests. Instrument-testing used validity and reliability test. Data analysis techniques used for the analysis include the prerequisite test, normality test, and homogeneity test. To test the hypothesis in this study, using a two-party t-test and one-party t-test. Based on the calculation of two-test and one-party t-test with 5% significant level and degree of freedom 68 on the calculation of t-test two parties obtained value tcount = 2.693058071> ttable = 1,99863, indicating that there are differences in learning outcomes mathematics students using cooperative learning models type TPS with students using cooperative learning models type TSTS. On the calculation of one t-test, tcount = 2,693058071> ttable = 1,99863 indicates that the TPS type is more effective than the TSTS type cooperative learning model in grade VIII students in even semester of SMP Negeri 2 Patikraja Banyumas regency teachings 2016/2017.